Bulgaria : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper examines inflation dynamics in Bulgaria from January 2012 to February 2015 and highlights some stylized facts about inflation in the country. January 2012 to February 2015 is the most relevant period for identifying factors contributing to recent deflation in Bulgaria, as well as their relative importance. Regression analysis suggests that during this period the inward spillover of low inflationary pressure from the European Union to Bulgaria has been the most significant factor, which was further exacerbated by consecutive electricity price cuts in 2013 and fast-falling global commodity prices, especially since late 2014.